2013
DOI: 10.1128/jvi.00124-13
|View full text |Cite
|
Sign up to set email alerts
|

A Carboxy-Terminally Truncated Human CPSF6 Lacking Residues Encoded by Exon 6 Inhibits HIV-1 cDNA Synthesis and Promotes Capsid Disassembly

Abstract: Since HIV-1 replication is modulated at multiple stages by host cell factors, identification and characterization of those host cell factors are expected to contribute to the development of novel anti-HIV therapeutics. Previous studies showed that a C-terminally truncated cytosolic form of cleavage and polyadenylation-specific factor 6 (CPSF6-358) inhibits HIV-1 infection through interference with HIV-1 trafficking to the nucleus. Here we identified and characterized a different configuration of C-terminally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 38 publications
4
45
0
Order By: Relevance
“…It also is possible that residual SUN2 in our shRNA-transduced cells masked any effect that might otherwise have been observed, as reported for the HIV integration cofactor LEDGF/p75 (93). It was previously observed that the silencing of CPSF6 did not modulate levels of HIV infection (12). However, the use of cytoplasmic CPSF6 provided a number of insights into HIV-host interactions, including an explanation for the effects of TNPO3 on HIV (28,94).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…It also is possible that residual SUN2 in our shRNA-transduced cells masked any effect that might otherwise have been observed, as reported for the HIV integration cofactor LEDGF/p75 (93). It was previously observed that the silencing of CPSF6 did not modulate levels of HIV infection (12). However, the use of cytoplasmic CPSF6 provided a number of insights into HIV-host interactions, including an explanation for the effects of TNPO3 on HIV (28,94).…”
Section: Discussionmentioning
confidence: 80%
“…CPSF6 plays a role in cellular mRNA processing and is localized to the nucleus by the importin-␤-family member TNPO3, which recognizes the C-terminal domain of CPSF6 (28). CPSF6 mutants lacking the C-terminal domain are located in the cytoplasm and inhibit HIV infection at nuclear entry (11) or before reverse transcription (12). The passaging of HIV in the presence of cytoplasmic murine CPSF6 selected for the CA N74D mutation, which uses alternative nucleoporins for nuclear entry (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular restriction factors TRIM5␣ and TRIMCyp have been shown to inhibit infection of multiple retroviruses by binding the capsid and inducing premature uncoating (7)(8)(9). Conversely, when CPSF6, which is normally located in the nucleus, is aberrantly localized in the cytoplasm, the uncoating of some retroviral capsids is slowed, resulting in decreased infection (10,11). Some of the inhibitory effects on HIV-1 infection associated with knockdown of TNP03, a nuclear import factor, may be due to secondary effects on CPSF6 localization (12)(13)(14).…”
mentioning
confidence: 99%
“…The MLV CA interacts with the cellular Friend virus susceptibility factor 1 (Fv1) (30). Binding of these proteins to capsids in the cytosol affects several postentry events (22,23,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), suggesting that the FL serves both structural and regulatory roles in the establishment of a new infection. As yet, no CA-binding host proteins have been identified in the alpharetroviruses.…”
mentioning
confidence: 99%